Preparation process of multispectral zinc sulfide crystal

Through magnetron sputtering plating of Pd film layer and thermal isostatic pressure treatment, the problem of fog layer at the edges of multispectral zinc sulfide crystal materials is solved, the utilization rate and production efficiency of the material are improved, and optical performance is improved.

CN119753602AActive Publication Date: 2025-04-04安徽光智科技有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411692487.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-04-04
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

In the existing multispectral zinc sulfide crystal preparation process, the crystal material obtained after thermal isostatic pressure treatment has a fog layer area on the surrounding edges, which causes it to be cut off during processing, which reduces the utilization rate of the material, and the stability of the metal foil wrapping treatment is poor and the pass rate is low.

Method used

The process of magnetron sputtering plating Pd film layer is adopted, including surface processing, ultrasonic cleaning, magnetron sputtering Pd film layer, thermal isostatic pressure treatment and optical cold processing, ensuring that the edges of the multispectral zinc sulfide crystal material are foggy-free and the overall foggy-free layer is not allowed.

Benefits of technology

The utilization rate of multispectral zinc sulfide crystals is improved, processing time is shortened, production efficiency and qualification rate is improved, and the optical performance is improved when processing special-shaped materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753602A_ABST
    Figure CN119753602A_ABST
Patent Text Reader

Abstract

The preparation process of the multispectral zinc sulfide crystal comprises the following steps: S1, carrying out surface processing treatment on a primary CVD zinc sulfide crystal material; s2, ultrasonic cleaning; and S3, plating a Pd film layer by magnetron sputtering: S31, filling a cleaned zinc sulfide crystal material into a sputtering chamber, S32, mounting a target material made of a metal Pd material, S33, vacuumizing the sputtering chamber, S34, setting working conditions: introducing argon, controlling the argon flow to be 20-200sccm, controlling the sputtering air pressure to be 0.1-1.0 Pa and controlling the sputtering temperature to be normal temperature, S35, plating the Pd film layer by sputtering, controlling the thickness to be 100-500nm, and only plating a bottom mounting surface, the method comprises the following steps of: (S36) after first-time film plating, enabling a sputtering chamber to reach external atmospheric pressure and taking out the sputtering chamber, (S37) loading the taken-out zinc sulfide crystal material into the sputtering chamber, taking the surface which is not plated with the film layer in the step (S35) as a surface to be plated with the film layer, and repeating sub-steps (S33), (S35) and (S36), so that the whole outer surface is plated with the Pd film layer; s4, hot isostatic pressing treatment; and S5, optical cold machining is carried out, and the Pd film layers on all the faces are removed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of crystal materials, and more specifically to a preparation process of multi-spectrum zinc sulfide crystals. Background Art

[0002] Multispectral zinc sulfide crystals are standard ZnS prepared by chemical vapor deposition (CVD) and obtained after hot isostatic pressing (HIP). It is currently the only infrared optical material other than diamond whose transmission band covers the entire band from visible light to long-wave infrared (8-12μm) and even the microwave band. Multispectral zinc sulfide is a chemically inert material with the characteristics of high purity, insolubility in water, moderate density, and easy processing. It is widely used in the production of infrared windows, fairings, and infrared optical components. Like zinc selenide materials, multispectral zinc sulfide is also a material with uniform and consistent refractive index and good image transmission performance. Compared with zinc selenide, multispectral zinc sulfide has high hardness, high fracture strength, and strong resistance to harsh environments. Multispectral zinc sulfide materials have shown their excellent wide-band transmission performance in both military and civilian applications, and have been widely used in high-speed missiles, aerospace, intelligent security, processing and manufacturing, forest fire prevention, and medical care.

[0003] The current method for preparing multi-spectral zinc sulfide is to wrap the zinc sulfide crystals prepared by CVD with metal foil, and then put them into a hot isostatic pressing furnace, and perform hot isostatic pressing under high temperature and high pressure conditions to obtain water-clear and transparent multi-spectral zinc sulfide. However, the multi-spectral zinc sulfide crystals obtained by this HIP treatment method will have fog layer areas of different widths on the edges (the fog layer is the area at the edges of the multi-spectral zinc sulfide crystals in a foggy state when illuminated by light in a dark room). When processing the multi-spectral zinc sulfide crystals, the fog layer areas at the edges need to be cut off, which will reduce the utilization rate of the multi-spectral zinc sulfide crystals. In addition, the metal foil wrapped zinc sulfide crystal treatment has poor stability and many defective products (i.e., low pass rate). Summary of the invention

[0004] In view of the problems existing in the background technology, an object of the present disclosure is to provide a preparation process of a multi-spectrum zinc sulfide crystal, wherein the prepared multi-spectrum zinc sulfide crystal material has no fog layer on the edge and has no fog layer on the whole.

[0005] Another object of the present disclosure is to provide a preparation process of multi-spectrum zinc sulfide crystals, which can improve the utilization rate of multi-spectrum zinc sulfide crystals, shorten processing time, improve production efficiency and reduce costs.

[0006] Another object of the present disclosure is to provide a preparation process of multi-spectrum zinc sulfide crystals, which is conducive to processing special-shaped zinc sulfide crystal materials.

[0007] Another object of the present disclosure is to provide a preparation process of multi-spectrum zinc sulfide crystals, which is beneficial to the stability of hot isostatic pressing treatment and improves the qualified rate.

[0008] Thus, a preparation process of multi-spectrum zinc sulfide crystals includes the following steps: S1, surface processing of native CVD zinc sulfide crystal materials to control the surface roughness of the native CVD zinc sulfide crystal materials to be Ra=0.1-1.5 μm; S2, ultrasonic cleaning; S3, magnetron sputtering coating of Pd film layers, including the following sub-steps: S31, loading the native CVD zinc sulfide crystal materials cleaned in step S2 into the sputtering chamber of a magnetron sputtering coating machine; S32, installing a target material made of metal Pd into the sputtering chamber; S33, evacuating the sputtering chamber to an absolute pressure of 1.0×10 -3 Pa, S34, set working conditions: introduce argon gas, the argon gas flow rate is 20-200sccm, the sputtering gas pressure is 0.1-1.0Pa, and the sputtering temperature is room temperature. S35, sputter-coat the surface of the native CVD zinc sulfide crystal material with a Pd film layer for the first time, and the thickness of the sputter-coated Pd film layer is 100-500nm. At this time, only the bottom installation surface of the native CVD zinc sulfide crystal material is not coated with the film layer, and the remaining surfaces of the surface of the native CVD zinc sulfide crystal material have been coated with the film layer. S36, after the first coating is completed, make the sputtering chamber reach the external atmospheric pressure, take out the native CVD zinc sulfide crystal material with the first sputter-coated Pd film layer, and avoid the native CVD zinc sulfide crystal material from being contaminated during the removal process. , S37, loading the coated surface of the native CVD zinc sulfide crystal material with the first sputtering Pd film layer into the sputtering chamber of the magnetron sputtering coating machine, and the surface without the film layer in step S35 is used as the surface to be coated facing the target material, and repeating sub-steps S33, S35, and S36 to obtain the native CVD zinc sulfide crystal material with the entire outer surface coated with a Pd film layer; S4, hot isostatic pressing treatment, to obtain the crystal material with the entire outer surface coated with a Pd film layer treated by hot isostatic pressing; S5, optical cold working, removing the Pd film layer on each surface of the crystal material with the entire outer surface coated with a Pd film layer treated by hot isostatic pressing, to obtain a multi-spectrum zinc sulfide crystal material, and the obtained multi-spectrum zinc sulfide crystal material has no fog layer on the edge and no fog layer as a whole.

[0009] The beneficial effects of the present disclosure are as follows.

[0010] According to the preparation process of the multi-spectrum zinc sulfide crystal disclosed in the present invention, through steps S1 to S5, the prepared multi-spectrum zinc sulfide crystal material has no fog layer on the edge and has no fog layer on the whole.

[0011] In the preparation process of the multi-spectral zinc sulfide crystal according to the present disclosure, since the prepared multi-spectral zinc sulfide crystal material has no fog layer on the edge and has no fog layer as a whole, when processing the multi-spectral zinc sulfide crystal, there is no operation of cutting off the fog layer area at the edges mentioned in the background technology, so it is possible to improve the utilization rate of the multi-spectral zinc sulfide crystal, shorten the processing time, improve production efficiency, and reduce costs.

[0012] In the preparation process of multi-spectral zinc sulfide crystals according to the present disclosure, since step S3 uses magnetron sputtering to plate a Pd film layer on the entire outer surface of the native CVD zinc sulfide crystal material, the Pd film layer plated on the entire outer surface and the native CVD zinc sulfide crystal material are in a gapless and integrally attached state, which is better than the state of close contact between the independent metal foil wrapped and the zinc sulfide crystal prepared by CVD in the background technology. The contact between the Pd film layer plated on the entire outer surface (whether it is the surrounding edges or the area outside the surrounding edges) and the native CVD zinc sulfide crystal material is more uniform, which is more conducive to processing special-shaped native CVD zinc sulfide crystal materials (such as spherical covers). In this way, in the hot isostatic pressing treatment in step S4, the promotion effect on the recrystallization of the zinc sulfide crystal material is more uniform, which is conducive to improving the optical properties including optical transmittance.

[0013] In the preparation process of multi-spectral zinc sulfide crystals according to the present disclosure, the thickness of the sputtered Pd film layer in step S3 is 100-500nm. It is difficult for the metal foil used for wrapping in the background technology to reach this level in thickness that can be used in actual production. This difficulty is not only reflected in the metal foil material itself, but also in the fact that the wrapping operation of the metal foil becomes very difficult. In other words, compared with the wrapped metal foil in the background technology, the sputtered Pd film layer of the preparation process of multi-spectral zinc sulfide crystals according to the present disclosure will completely wrap the Pd material of the native CVD zinc sulfide crystal material thinner, and the wrapping operation is simpler, more convenient and effective. Further, this thinner wrapping will be more conducive to the temperature and pressure of hot isostatic pressing, more conducive to shortening the hot isostatic pressing treatment time, more conducive to the stability of the hot isostatic pressing treatment, and improve the qualified rate.

[0014] In the preparation process of multi-spectral zinc sulfide crystals according to the present disclosure, the surface processing in step S1 is helpful for the adhesion of the Pd film layer and improves the bonding tightness between the Pd film layer and the native CVD zinc sulfide crystal material. The Pd film layer in step S3 is produced by magnetron sputtering, which further enhances the bonding tightness between the Pd film layer and the native CVD zinc sulfide crystal material. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a photograph of the multi-spectral zinc sulfide crystal material prepared in Example 1.

[0016] Figure 2 This is a transmittance curve of the multi-spectral zinc sulfide crystal material prepared in Example 1 in the 0.4-0.8 μm band.

[0017] Figure 3 This is a transmittance curve of the multi-spectral zinc sulfide crystal material prepared in Example 1 in the 8-12 μm band.

[0018] Figure 4 This is a photograph of the multi-spectral zinc sulfide crystal material prepared in Example 2.

[0019] Figure 5 This is a transmittance curve of the multi-spectral zinc sulfide crystal material prepared in Example 2 in the 0.4-0.8 μm band.

[0020] Figure 6 This is a transmittance curve of the multi-spectral zinc sulfide crystal material prepared in Example 2 in the 8-12 μm band.

[0021] Figure 7 This is a photograph of the multi-spectral zinc sulfide crystal material prepared in Example 3.

[0022] Figure 8 This is a transmittance curve of the multi-spectral zinc sulfide crystal material prepared in Example 3 in the 0.4-0.8 μm band.

[0023] Fig. 9 This is a transmittance curve of the multi-spectral zinc sulfide crystal material prepared in Example 3 in the 8-12 μm band.

[0024] Fig.10 This is a photograph of the multi-spectral zinc sulfide crystal material prepared in Example 4.

[0025] Fig.11 This is a transmittance curve of the multi-spectral zinc sulfide crystal material prepared in Example 4 in the 0.4-0.8 μm band.

[0026] Fig.12 This is a transmittance curve of the multi-spectral zinc sulfide crystal material prepared in Example 4 in the 8-12 μm band. DETAILED DESCRIPTION

[0027] It will be understood that the disclosed embodiments are merely examples of the present disclosure, which may be implemented in various forms, and therefore, the specific details disclosed herein should not be interpreted as limiting, but merely as a basis for the claims and as a representative basis for teaching one of ordinary skill in the art to implement the present disclosure in various ways.

[0028] [Preparation process of multi-spectrum zinc sulfide crystals]

[0029] The preparation process of multi-spectrum zinc sulfide crystals according to the present disclosure comprises the steps of:

[0030] S1, surface processing of the native CVD zinc sulfide crystal material, so that the surface roughness of the native CVD zinc sulfide crystal material is controlled to be Ra=0.1-1.5μm;

[0031] S2, ultrasonic cleaning;

[0032] S3, magnetron sputtering to deposit a Pd film layer, including sub-steps:

[0033] S31, loading the native CVD zinc sulfide crystal material cleaned in step S2 into the sputtering chamber of a magnetron sputtering coating machine,

[0034] S32, installing a target made of metal Pd into a sputtering chamber;

[0035] S33, evacuate the sputtering chamber to an absolute pressure of 1.0×10 -3 Pa;

[0036] S34, setting working conditions: introducing argon gas, the argon gas flow rate is 20-200 sccm, the sputtering gas pressure is 0.1-1.0 Pa, and the sputtering temperature is room temperature;

[0037] S35, sputtering a Pd film layer on the surface of the native CVD zinc sulfide crystal material for the first time, the thickness of the sputtered Pd film layer is 100-500nm, at this time, only the bottom mounting surface of the native CVD zinc sulfide crystal material is not coated with the film layer, and the rest of the surfaces of the native CVD zinc sulfide crystal material are coated with the film layer;

[0038] S36, after the first coating is completed, the sputtering chamber is made to reach the external atmospheric pressure, and the native CVD zinc sulfide crystal material of the first sputtering Pd film layer is taken out, and the native CVD zinc sulfide crystal material is prevented from being contaminated during the taking out process;

[0039] S37, loading the coated surface of the native CVD zinc sulfide crystal material with the first sputtering Pd film into the sputtering chamber of the magnetron sputtering coating machine, with the surface without the film layer in step S35 facing the target material as the surface to be coated, repeating sub-steps S33, S35, and S36 to obtain the native CVD zinc sulfide crystal material with the entire outer surface coated with the Pd film layer;

[0040] S4, hot isostatic pressing to obtain a crystalline material with a Pd film layer on the entire outer surface after hot isostatic pressing;

[0041] S5, optical cold processing, removing the Pd film layers on all surfaces of the crystal material coated with the Pd film layer on the entire outer surface after hot isostatic pressing, to obtain a multi-spectrum zinc sulfide crystal material, wherein the obtained multi-spectrum zinc sulfide crystal material has no fog layer on the edge and has no fog layer on the whole.

[0042] In the preparation process of the multi-spectrum zinc sulfide crystal according to the present disclosure, through steps S1 to S5, the prepared multi-spectrum zinc sulfide crystal material has no fog layer on the edge and has no fog layer on the whole.

[0043] In the preparation process of the multi-spectral zinc sulfide crystal according to the present disclosure, since the prepared multi-spectral zinc sulfide crystal material has no fog layer on the edge and has no fog layer as a whole, when processing the multi-spectral zinc sulfide crystal, there is no operation of cutting off the fog layer area at the edges mentioned in the background technology, so it is possible to improve the utilization rate of the multi-spectral zinc sulfide crystal, shorten the processing time, improve production efficiency, and reduce costs.

[0044] In the preparation process of multi-spectral zinc sulfide crystals according to the present disclosure, since step S3 uses magnetron sputtering to plate a Pd film layer on the entire outer surface of the native CVD zinc sulfide crystal material, the Pd film layer plated on the entire outer surface and the native CVD zinc sulfide crystal material are in a gapless and integrally attached state, which is better than the state of close contact between the independent metal foil wrapped and the zinc sulfide crystal prepared by CVD in the background technology. The contact between the Pd film layer plated on the entire outer surface (whether it is the surrounding edges or the area outside the surrounding edges) and the native CVD zinc sulfide crystal material is more uniform, which is more conducive to processing special-shaped native CVD zinc sulfide crystal materials (such as spherical covers). In this way, in the hot isostatic pressing treatment in step S4, the promotion effect on the recrystallization of the zinc sulfide crystal material is more uniform, which is conducive to improving the optical properties including optical transmittance.

[0045] In the preparation process of multi-spectral zinc sulfide crystals according to the present disclosure, the thickness of the sputtered Pd film layer in step S3 is 100-500nm. It is difficult for the metal foil used for wrapping in the background technology to reach this level in thickness that can be used in actual production. This difficulty is not only reflected in the metal foil material itself, but also in the fact that the wrapping operation of the metal foil becomes very difficult. In other words, compared with the wrapped metal foil in the background technology, the sputtered Pd film layer of the preparation process of multi-spectral zinc sulfide crystals according to the present disclosure will completely wrap the Pd material of the native CVD zinc sulfide crystal material thinner, and the wrapping operation is simpler, more convenient and effective. Further, this thinner wrapping will be more conducive to the temperature and pressure of hot isostatic pressing, more conducive to shortening the hot isostatic pressing treatment time, more conducive to the stability of the hot isostatic pressing treatment, and improve the qualified rate.

[0046] In the preparation process of multi-spectral zinc sulfide crystals according to the present disclosure, the surface processing in step S1 is helpful for the adhesion of the Pd film layer and improves the bonding tightness between the Pd film layer and the native CVD zinc sulfide crystal material. The Pd film layer in step S3 is produced by magnetron sputtering, which further enhances the bonding tightness between the Pd film layer and the native CVD zinc sulfide crystal material.

[0047] In one example, in step S1, a CVD method is used to grow native zinc sulfide crystal material. The process of growing native zinc sulfide crystal by the CVD method is as follows: using a Zn-H2S reaction system, a ZnS crystal material is grown in a chemical vapor deposition furnace. The deposition device in the furnace mainly includes a crucible, a deposition chamber, and a discharge box, all of which are made of isostatic graphite material; the crucible is responsible for melting and evaporating the raw material solid zinc, the heating temperature is 600°C, and ZnS is grown in the deposition chamber; the deposition chamber and the crucible are connected by a partition with an internally designed gas path nozzle, and the hydrogen sulfide gas and the molten and evaporated hydrogen sulfide in the crucible are connected to each other. Zinc vapor is injected into the deposition chamber by the carrier gas argon through the respective gas paths to the nozzle, and is transmitted to the surface of the graphite mold substrate to undergo a chemical reaction to generate ZnS; the heating temperature of the deposition chamber is 660°C; the unreacted gaseous reactants, the reaction by-product hydrogen, and the zinc sulfide particles that have not been effectively deposited will enter the discharge box with the carrier gas, and the gaseous substances will then enter the exhaust gas treatment system; after the reaction is completed, the introduction of hydrogen sulfide is stopped, the crucible heating is stopped, and the temperature is naturally cooled; the temperature of the deposition chamber is reduced to room temperature at a cooling rate of 0.1-0.5°C / min; and the ZnS crystal material is taken out of the furnace.

[0048] For example, in step S1, the surface processing is performed by grinding, wherein the surface of the native CVD zinc sulfide crystal material is ground to a surface roughness Ra of 0.1-1.5 μm by using a grinder, and the abrasive is 600 mesh corundum powder purchased from Zhengzhou Xinli Wear Resistant Materials Co., Ltd.

[0049] In step S1 , the native CVD zinc sulfide crystal material may be, but is not limited to, a flat plate material or a spherical cover.

[0050] In one example, in step S2, ultrasonic cleaning is to use an eight-slot ultrasonic cleaning machine to process the native CVD zinc sulfide crystal material in the order of 1-8, and the whole process lasts for more than 20 minutes; the functions of each slot are as follows: slot 1: ultrasonic washing, using the original solution of the grinding and polishing cleaning agent of the Xinmingyang brand at room temperature, slot 2: ultrasonic washing, using the optical glass cleaning agent of the Feinel brand, and preparing a 5%-7% cleaning solution with pure water in proportion, the cleaning temperature is 60°C, slot 3: ultrasonic washing, using the same cleaning solution as slot 2, the cleaning temperature is 50°C, slot 4: pure water ultrasound at room temperature, slot 5: pure water ultrasound at room temperature, slot 6: pure water ultrasound at room temperature, slot 7: slow air dehydration, slot 8: hot air drying, the drying temperature is 50°C. Further, the whole process lasts for 30-40 minutes.

[0051] In one example, in sub-step S32, the purity of the metal Pd target material is not less than 4N.

[0052] In one example, in sub-step S33, the sputtering chamber is first roughly evacuated to 5 Pa using a mechanical pump, and then finely evacuated to an absolute pressure of 1.0×10 -3 Pa.

[0053] In one example, in sub-step S34, the flow rate of argon gas is controlled by a mass flow controller (MFC).

[0054] In one example, in sub-step S35, the thickness of the sputtered Pd film layer is monitored by using a crystal oscillator method using a corresponding crystal oscillator of a plurality of crystal oscillators of a crystal controller, and the crystal oscillator frequency is not less than 5.99 MHz.

[0055] In one example, in sub-step S36, after coating is completed, the power of the magnetron sputtering coating machine is turned off, argon gas is slowly filled in, and the gas valve of the magnetron sputtering coating machine is used to control the gas intake rate so that the sputtering chamber of the magnetron sputtering coating machine returns to the external atmospheric pressure in no less than 20 minutes.

[0056] In one example, the hot isostatic pressing process in step S4 includes sub-steps:

[0057] S41, installing the crystal material whose entire outer surface is coated with a Pd film layer in step S3 in a hot isostatic pressing furnace chamber;

[0058] S42, furnace closing and furnace washing;

[0059] S43, filling the furnace chamber with cold argon gas at 30-60 MPa, and then starting to heat up to a target temperature of 900-1050°C at a heating rate of 0.5-5°C / min, and replenishing argon gas during the heating process to make the hot isostatic pressing furnace chamber reach a target pressure of 100-200 MPa;

[0060] S44, maintaining target temperature and pressure for 10-120 hours;

[0061] S45, after the heat preservation is completed, the temperature is lowered to room temperature at a rate of ≤5°C / min;

[0062] S46, reduce the pressure to normal pressure, take out of the furnace, and take out the product.

[0063] Further, for example, in sub-step 42, after the furnace is closed, it is evacuated and then filled with argon gas with a purity of not less than 5N, and the evacuation and filling are repeated more than 5 times to clean the furnace.

[0064] Further, for example, in sub-step 43, the purity of argon gas is not less than 5N.

[0065] In one example, in step S5, the optical cold working adopts a surface grinding process. For example, the grinding is performed using a grinder, and the abrasive is 600-mesh corundum powder purchased from Zhengzhou Xinli Wear-Resistant Materials Co., Ltd.

[0066] In one example, the preparation process of the multi-spectral zinc sulfide crystal according to the present disclosure further includes: step S6, preparing a test sample of the multi-spectral zinc sulfide crystal material, and performing optical performance testing, the test results are: the average transmittance in the 0.4-0.8μm band is 69.95-70.72%, and the average transmittance in the 8-12μm band is 70.73-75.0%. Further, the test results are: the volume absorption coefficient is 0.10-0.13cm -1 The temperature coefficient of refractive index in the 10.6 μm band is (31-36)×10 -6 / ℃, the refractive index uniformity in the 0.6328μm band is (15-18)×10 -6 .

[0067] [test]

[0068] Example 1

[0069] The preparation process of the multi-spectrum zinc sulfide crystal of Example 1 adopts the following steps:

[0070] S1, surface processing of the native CVD zinc sulfide crystal material, so that the surface roughness of the native CVD zinc sulfide crystal material is controlled at Ra = 1.2 μm,

[0071] in,

[0072] The CVD method is used to grow native zinc sulfide crystal material. The process of growing native zinc sulfide crystal by the CVD method is as follows: using a Zn-H2S reaction system, ZnS crystal material is grown in a chemical vapor deposition furnace. The deposition device in the furnace mainly includes a crucible, a deposition chamber, and a discharge box, all of which are made of isostatic graphite material; the crucible is responsible for melting and evaporating the raw material solid zinc, the heating temperature is 600°C, and ZnS is grown in the deposition chamber; the deposition chamber and the crucible are connected by a partition with an internal gas path nozzle, and the hydrogen sulfide gas and the molten and evaporated zinc vapor in the crucible are injected into the deposition chamber by the carrier gas argon through their respective gas paths to the nozzle and transmitted to A chemical reaction occurs on the surface of the graphite mold substrate to generate ZnS; the heating temperature of the deposition chamber is 660°C; the unreacted gaseous reactants, the reaction byproduct hydrogen, and the zinc sulfide particles that have not been effectively deposited will enter the discharge box along with the carrier gas, and the gaseous substances will then enter the tail gas treatment system; after the reaction is completed, the introduction of hydrogen sulfide is stopped, the crucible heating is stopped, and the temperature is naturally reduced; the temperature of the deposition chamber is reduced to room temperature at a cooling rate of 0.3°C / min; the ZnS crystal material is taken out of the furnace, and the blank (i.e., the obtained ZnS crystal material) is selected and processed into a flat plate with a specification of 200mm×200mm×22mm;

[0073] The surface processing adopts grinding, which is to grind the surface of the original CVD zinc sulfide crystal material to a surface roughness Ra1,2μm by using a grinder, and the abrasive adopts 600 mesh corundum powder purchased from Zhengzhou Xinli Wear-resistant Materials Co., Ltd.;

[0074] S2, ultrasonic cleaning,

[0075] Among them, ultrasonic cleaning is carried out by using an eight-slot ultrasonic cleaning machine, and the native CVD zinc sulfide crystal material is placed into the slots in the order of 1-8 for treatment. The whole process lasts for 35 minutes; the functions of each slot are as follows: slot 1: washing ultrasonic, using the grinding and polishing cleaning agent of Xinmingyang brand at room temperature, slot 2: washing ultrasonic, using the optical glass cleaning agent of Feinell brand, and preparing a 6% cleaning solution with pure water in proportion, and the cleaning temperature is 60°C, slot 3: washing ultrasonic, using the same cleaning solution as slot 2, and the cleaning temperature is 50°C, slot 4: pure water ultrasound at room temperature, slot 5: pure water ultrasound at room temperature, slot 6: pure water ultrasound at room temperature, slot 7: slow pull

[0076] Air dehydration, slot 8: hot air drying, drying temperature 50°C;

[0077] S3, magnetron sputtering coating of Pd film, using the following sub-steps:

[0078] S31, loading the native CVD zinc sulfide crystal material cleaned in step S2 into the sputtering chamber of a magnetron sputtering coating machine,

[0079] S32, installing a target material made of metal Pd into a sputtering chamber, wherein the purity of the target material made of metal Pd is 4N;

[0080] S33, evacuate the sputtering chamber. First, roughly evacuate the sputtering chamber to 5 Pa using a mechanical pump, and then use a molecular pump to evacuate the chamber to an absolute pressure of 1.0×10 -3 Pa;

[0081] S34, set the working conditions: introduce argon gas, the argon flow rate is 50sccm, the sputtering pressure is 0.5Pa, the sputtering temperature is room temperature, and the argon flow rate is controlled by a mass flow controller (MFC)

[0082] control;

[0083] S35, sputtering a Pd film layer on the surface of the native CVD zinc sulfide crystal material for the first time, the thickness of the sputtered Pd film layer is 200nm, at this time, only the bottom mounting surface of the zinc sulfide crystal material is not coated with the film layer, and the remaining surfaces of the surface of the zinc sulfide crystal material are coated with the film layer, the thickness of the sputtered Pd film layer is monitored by using a crystal oscillator method using a corresponding crystal oscillator of a plurality of crystal oscillators of a crystal controller, and the crystal oscillator frequency is not less than 5.99MHz;

[0084] S36, after the first coating is completed, turn off the power of the magnetron sputtering coating machine, slowly fill it with argon gas, use the gas valve of the magnetron sputtering coating machine to control the gas intake rate, so that the sputtering chamber of the magnetron sputtering coating machine returns to the external atmospheric pressure within 20 minutes, take out the crystal material of the first sputtering Pd film layer, and prevent the crystal material from being contaminated during the taking out process;

[0085] S37, loading the coated surface of the crystal material with the first sputtering Pd film into the sputtering chamber of the magnetron sputtering coating machine, with the surface without the film layer in step S35 as the surface to be coated facing the target material, repeating sub-steps S33, S35, and S36 to coat the surface to be coated with the Pd film layer, and obtaining the crystal material with the entire outer surface coated with the Pd film layer;

[0086] S4, hot isostatic pressing to obtain a crystalline material with a Pd film layer on the entire outer surface after hot isostatic pressing.

[0087] The hot isostatic pressing process uses the following sub-steps:

[0088] S41, installing the crystal material whose entire outer surface is coated with a Pd film layer in step S3 in a hot isostatic pressing furnace chamber;

[0089] S42, closing the furnace and cleaning the furnace. After closing the furnace, evacuate the furnace and then fill it with argon gas with a purity of 5N. Vacuum and fill it more than 5 times to clean the furnace.

[0090] S43, 40 MPa of argon gas with a purity of 5N is filled into the furnace chamber in a cold state, and then the temperature is raised to a target temperature of 960°C at a heating rate of 1.5°C / min. Argon gas is added during the heating process to make the hot isostatic pressing furnace chamber reach a target pressure of 150 MPa;

[0091] S44, maintain target temperature and pressure for 60 hours;

[0092] S45, after the heat preservation is completed, the temperature is lowered to room temperature at a rate of 1°C / min;

[0093] S46, reducing the pressure to normal pressure, taking out the product from the furnace;

[0094] S5, optical cold working, removing the Pd film layer on each surface of the crystal material coated with the Pd film layer on the entire outer surface after hot isostatic pressing, to obtain a multi-spectral zinc sulfide crystal material, wherein the optical cold working adopts a surface grinding process, the grinding is performed by using a grinder, and the abrasive is 600 mesh corundum powder purchased from Zhengzhou Xinli Wear-Resistant Materials Co., Ltd.;

[0095] Step S6, preparing a test sample of a multi-spectral zinc sulfide crystal material and performing an optical performance test, wherein the thickness of the test sample is 9.5 mm.

[0096] Example 2

[0097] Except for the following differences, the rest is the same as Example 1:

[0098] In step S1, the specification is 300mm×300mm×28mm flat plate material;

[0099] In sub-step S34, the argon gas flow rate is 80 sccm and the sputtering gas pressure is 0.8 Pa;

[0100] In sub-step S35, the thickness of the sputtered Pd film layer is 300 nm;

[0101] In sub-step S43, the target pressure is 160 MPa;

[0102] In sub-step S44, the duration is 70 hours;

[0103] In step S6, the thickness of the test sample is 5 mm.

[0104] Example 3

[0105] Except for the following differences, the rest is the same as Example 1:

[0106] In step S1, the specifications are convex curvature Rcx68, concave curvature Rcc60, total height Th56, center thickness CT8, and 134mm diameter ball cover, and the roughness is controlled at Ra=1.4μm;

[0107] In step S6, the thickness of the test sample is 5 mm.

[0108] Example 4

[0109] Except for the following differences, the rest is the same as Example 2:

[0110] In step S1, the specifications are convex curvature Rcx106, concave curvature Rcc93.5, total height Th106, center thickness CT12.5, and diameter 212mm, and the roughness is controlled at Ra=1.4μm;

[0111] In step S6, the thickness of the test sample is 1 mm.

[0112] Figure 1 This is a photograph of the multi-spectral zinc sulfide crystal material prepared in Example 1. Figure 2 It is a transmittance curve of the multi-spectral zinc sulfide crystal material (ie, the test sample) prepared in Example 1 in the 0.4-0.8 μm band. Figure 3 It is a transmittance curve of the multi-spectral zinc sulfide crystal material (ie, the test sample) prepared in Example 1 in the 8-12 μm band.

[0113] Figure 4 This is a photograph of the multi-spectral zinc sulfide crystal material prepared in Example 2. Figure 5 It is a transmittance curve of the multi-spectral zinc sulfide crystal material (ie, the test sample) prepared in Example 2 in the 0.4-0.8 μm band. Figure 6 It is a transmittance curve of the multi-spectral zinc sulfide crystal material (ie, the test sample) prepared in Example 2 in the 8-12 μm band.

[0114] Figure 7 This is a photograph of the multi-spectral zinc sulfide crystal material prepared in Example 3. Figure 8 It is a transmittance curve of the multi-spectral zinc sulfide crystal material (ie, the test sample) prepared in Example 3 in the 0.4-0.8 μm band. Fig. 9 It is a transmittance curve of the multi-spectral zinc sulfide crystal material (ie, the test sample) prepared in Example 3 in the 8-12 μm band.

[0115] Fig.10 This is a photograph of the multi-spectral zinc sulfide crystal material prepared in Example 4. Fig.11 It is a transmittance curve of the multi-spectral zinc sulfide crystal material (ie, the test sample) prepared in Example 4 in the 0.4-0.8 μm band. Fig.12 It is a transmittance curve of the multi-spectral zinc sulfide crystal material (ie, the test sample) prepared in Example 4 in the 8-12 μm band.

[0116] from Figure 1 , Figure 4 , Figure 7 and Fig.10 It can be seen that no matter it is a flat plate material or a spherical cover, the multi-spectrum zinc sulfide crystal material obtained in Examples 1-4 has no fog layer on the edge and has no fog layer on the whole.

[0117] based on Figure 2 and Figure 3 The multi-spectral zinc sulfide crystal material prepared in Example 2 has an average transmittance of 70.45% in the 0.4-0.8 μm band and an average transmittance of 74.97% in the 8-12 μm band.

[0118] based on Figure 5 and Figure 6 The multi-spectral zinc sulfide crystal material prepared in Example 3 has an average transmittance of 70.55% in the 0.4-0.8 μm band and an average transmittance of 70.73% in the 8-12 μm band.

[0119] based on Figure 8 and Fig. 9 The multi-spectral zinc sulfide crystal material prepared in Example 3 has an average transmittance of 69.95% in the 0.4-0.8 μm band and an average transmittance of 71.1% in the 8-12 μm band.

[0120] based on Fig.11 and Fig.12 The multi-spectral zinc sulfide crystal material prepared in Example 4 has an average transmittance of 70.72% in the 0.4-0.8 μm band and an average transmittance of 75.0% in the 8-12 μm band.

[0121] In addition, other optical performance test results of the test samples of Examples 1-4 are as follows:

[0122] Example 1: Volume absorption coefficient 0.11 cm -1 The temperature coefficient of refractive index at 10.6 μm is 36×10 -6 / ℃, the refractive index uniformity at 0.6328μm is 18×10 -6 ;

[0123] Example 2: Volume absorption coefficient 0.13 cm -1 The temperature coefficient of refractive index at 10.6 μm is 34×10 -6 / ℃, the refractive index uniformity at 0.6328μm is 16×10 -6 ;

[0124] Example 3: Volume Absorption Coefficient 0.10 cm -1 The temperature coefficient of refractive index is 33×10 at 10.6 μm. -6 / ℃, the refractive index uniformity at 0.6328μm is 15×10 -6 ;

[0125] Example 4: Volume absorption coefficient 0.12 cm -1 The temperature coefficient of refractive index is 31×10 at 10.6 μm. -6 / ℃, the refractive index uniformity at 0.6328μm is 16×10 -6 .

[0126] The above detailed description is used to describe multiple exemplary embodiments, but this document is not intended to be limited to the explicitly disclosed combinations. Therefore, unless otherwise stated, the various features disclosed herein can be combined together to form multiple additional combinations that are not shown for the sake of simplicity.

Claims

1. A preparation process of multi-spectrum zinc sulfide crystals, characterized in that: Includes steps: S1, surface processing of the native CVD zinc sulfide crystal material, so that the surface roughness of the native CVD zinc sulfide crystal material is controlled to be Ra=0.1-1.5μm; S2, ultrasonic cleaning; S3, magnetron sputtering to deposit a Pd film layer, including sub-steps: S31, loading the native CVD zinc sulfide crystal material cleaned in step S2 into the sputtering chamber of a magnetron sputtering coating machine, S32, installing a target made of metal Pd into a sputtering chamber; S33, evacuate the sputtering chamber to an absolute pressure of 1.0×10 -3 Pa; S34, setting working conditions: introducing argon gas, the argon gas flow rate is 20-200 sccm, the sputtering gas pressure is 0.1-1.0 Pa, and the sputtering temperature is room temperature; S35, sputtering a Pd film layer on the surface of the native CVD zinc sulfide crystal material for the first time, the thickness of the sputtered Pd film layer is 100-500nm, at this time, only the bottom mounting surface of the native CVD zinc sulfide crystal material is not coated with the film layer, and the rest of the surfaces of the native CVD zinc sulfide crystal material are coated with the film layer; S36, after the first coating is completed, the sputtering chamber is made to reach the external atmospheric pressure, and the native CVD zinc sulfide crystal material of the first sputtering Pd film layer is taken out, and the native CVD zinc sulfide crystal material is prevented from being contaminated during the taking out process; S37, loading the coated surface of the native CVD zinc sulfide crystal material with the first sputtering Pd film into the sputtering chamber of the magnetron sputtering coating machine, with the surface without the film layer in step S35 facing the target material as the surface to be coated, repeating sub-steps S33, S35, and S36 to obtain the native CVD zinc sulfide crystal material with the entire outer surface coated with the Pd film layer; S4, hot isostatic pressing to obtain a crystalline material with a Pd film layer on the entire outer surface after hot isostatic pressing; S5, optical cold processing, removing the Pd film layers on all surfaces of the crystal material coated with the Pd film layer on the entire outer surface after hot isostatic pressing, to obtain a multi-spectrum zinc sulfide crystal material, wherein the obtained multi-spectrum zinc sulfide crystal material has no fog layer on the edge and has no fog layer on the whole.

2. The preparation process of multi-spectrum zinc sulfide crystal according to claim 1, characterized in that: In step S1, a CVD method is used to grow a native zinc sulfide crystal material. The process of growing a native zinc sulfide crystal by the CVD method is as follows: using a Zn-H2S reaction system, a ZnS crystal material is grown in a chemical vapor deposition furnace. The deposition device in the furnace mainly includes a crucible, a deposition chamber, and a discharge box, all of which are made of isostatic graphite material; the crucible is responsible for melting and evaporating the raw material solid zinc, the heating temperature is 600°C, and ZnS is grown in the deposition chamber; the deposition chamber and the crucible are connected by a partition with an internally designed gas path nozzle, and the hydrogen sulfide gas and the molten and evaporated zinc vapor in the crucible are The carrier gas argon reaches the nozzle through the respective gas paths and is injected into the deposition chamber, and is transmitted to the surface of the graphite mold substrate to undergo a chemical reaction to generate ZnS; the heating temperature of the deposition chamber is 660°C; the unreacted gas reactants, the reaction by-product hydrogen and the zinc sulfide particles that have not been effectively deposited will enter the discharge box with the carrier gas, and the gaseous substances will then enter the exhaust gas treatment system; after the reaction is completed, the introduction of hydrogen sulfide is stopped, the crucible heating is stopped, and the temperature is naturally cooled; the temperature of the deposition chamber is reduced to room temperature at a cooling rate of 0.1-0.5°C / min; and the ZnS crystal material is taken out of the furnace.

3. The preparation process of multi-spectrum zinc sulfide crystal according to claim 1, characterized in that: In step S1 , the native CVD zinc sulfide crystal material is a flat plate material or a spherical cover.

4. The preparation process of multi-spectrum zinc sulfide crystal according to claim 1, characterized in that: In step S2, ultrasonic cleaning is performed using an eight-slot ultrasonic cleaning machine, and the native CVD zinc sulfide crystal material is placed into the slots for treatment in the order of 1-8, and the whole process lasts for more than 20 minutes; the functions of each slot are respectively, slot 1: washing ultrasonic, using the grinding and polishing cleaning agent stock solution of Xinmingyang brand at room temperature, slot 2: washing ultrasonic, using the optical glass cleaning agent of Feinel brand, and mixed with pure water in proportion to form a 5%-7% cleaning solution, and the cleaning temperature is 60°C, slot 3: washing ultrasonic, using the same cleaning solution as slot 2, and the cleaning temperature is 50°C, slot 4: pure water ultrasonic at room temperature, slot 5: pure water ultrasonic at room temperature, slot 6: pure water ultrasonic at room temperature, slot 7: slow air dehydration, slot 8: hot air drying, and the drying temperature is 50°C.

5. The preparation process of multi-spectrum zinc sulfide crystal according to claim 1, characterized in that: In sub-step S32, the purity of the target material made of metal Pd is not less than 4N.

6. The preparation process of multi-spectrum zinc sulfide crystal according to claim 1, characterized in that: Step S4 includes the sub-steps of: S41, installing the crystal material whose entire outer surface is plated with a Pd film layer in step S3 in a hot isostatic pressing furnace chamber; S42, furnace closing and furnace washing; S43, filling the furnace chamber with cold argon gas at 30-60 MPa, and then starting to heat up to a target temperature of 900-1050°C at a heating rate of 0.5-5°C / min, and replenishing argon gas during the heating process to make the hot isostatic pressing furnace chamber reach a target pressure of 100-200 MPa; S44, maintain target temperature and pressure for 10-120 hours; S45, after the heat preservation is completed, the temperature is lowered to room temperature at a rate of ≤5°C / min; S46, reduce the pressure to normal pressure, take out of the furnace, and take out the product.

7. The preparation process of multi-spectrum zinc sulfide crystal according to claim 6, characterized in that: In sub-step 43, the purity of argon gas is not less than 5N.

8. The preparation process of multi-spectrum zinc sulfide crystal according to claim 1, characterized in that: In step S5, the optical cold working adopts a surface grinding process.

9. The preparation process of multi-spectrum zinc sulfide crystal according to claim 1, characterized in that: The preparation process of the multi-spectrum zinc sulfide crystal also includes: Step S6, preparing a test sample of a multi-spectral zinc sulfide crystal material and performing optical performance testing, the test results are: The average transmittance in the 0.4-0.8μm band is 69.95-70.72%. The average transmittance in the 8-12μm band is 70.73-75.0%.

10. The preparation process of multi-spectrum zinc sulfide crystal according to claim 9, characterized in that: The test results also showed: The body absorption coefficient is 0.10-0.13cm -1 , The temperature coefficient of refractive index in the 10.6 μm band is (31-36)×10 -6 / ℃, The refractive index uniformity in the 0.6328μm band is (15-18)×10 -6 .

Citation Information

Patent Citations

  • Multi-spectrum protective film and preparation method thereof

    CN102912293A

  • Preparation method of multispectral zinc sulfide

    CN115403384A

  • Magnetron sputtering coating process and method for surface of composite material

    CN117187765A

  • Optical recording medium with phase-change type optical disk protective film composed essentially of zinc sulfide formed by using sputtering target composed essentially of zinc sulfide

    JP2008159242A

  • Hydrogen-permeable membrane and method for manufacturing the same

    JP2009045539A